Fatigue Tests Of New Assembly Bolt Connections For Perspective Temporary Steel Railway Bridges - Karmazínová, Marcela; Štrba, Michal; Pilgr, Milan (Zenodo, 2015)
The paper deals with the problems of the actual behavior, failure mechanism and load-carrying capacity of the special bolt connection developed and intended for the assembly connections of truss main girders of perspective railway temporary steel bridges. Within the framework of this problem solution, several types of structural details of assembly joints have been considered as the conceptual structural design. Based on the preliminary evaluation of advantages or disadvantages of these ones, in principle two basic structural configurations – so-called “tooth” and “splice-plate” connections have been selected for the subsequent detailed investigation. This investigation is mainly based on the experimental verification of the actual behavior, strain and failure mechanism and corresponding strength of the connection, and on its numerical modeling using FEM. This paper is focused only on the cyclic loading (fatigue) tests results of “splice-plate” connections and their evaluation, which have already been finished. Simultaneously with the fatigue tests, the static loading tests have been realized too, but these ones, as well as FEM numerical modeling, are not the subject of this paper. : {"references": ["M. Karmaz\u00ednov\u00e1 and M. \u0160trba, \"Static loading tests of new type of bolt\nassembly connection developed for perspective temporary steel railway\nbridges\", Applied Mechanics and Materials, Trans Tech Publications:\nZurich, Vol. 590, 2014, pp. 331-335, doi: 10.4028/www.scientific.net/\nAMM.590.331. ISSN 1660-9336.", "M. Karmaz\u00ednov\u00e1, \"Fatigue tests of assembly joints of truss main girders\nof temporary footbridge for pedestrians and cyclists\", Applied\nMechanics and Materials, Trans Tech Publications: Zurich, Vol. 405-\n408, 2013, pp. 1598-1601, doi: 10.4028/ www.scientific.net/AMM.405-\n408.1598. ISSN 1660-9336.", "M. Karmaz\u00ednov\u00e1 and P. Simon, \"Fatigue tests of assembly joints of truss\nmain girders of newly developed temporary footbridges\", International\nJournal of Mechanics, NAUN: U.S.A., Vol. 7, 2013, Issue 4, pp. 475-\n483. ISSN 1998-4448.", "M. \u0160trba, \"On the problems of testing methodology used in case of the\ntemporary steel through truss footbridge development\", International\nJournal of Mechanics, North Atlantic University Union: U.S.A., Issue 2,\nVol. 7, 2013, pp. 73-80. ISSN 1998-4448.", "M. Karmaz\u00ednov\u00e1 and J. Melcher, \"Material testing and evaluation of\nsteel mechanical properties for classification of steel grade of existing\ncivil engineering structure\", Advanced Materials Research, Trans Tech\nPublications: Z\u00fcrich, Vol. 651, 2013, pp. 274-279, doi: 10.4028/www.\nscientific.net/AMR.651.274. ISSN 1022-6680.", "J. Melcher, \"Full-scale testing of steel and timber structures: Examples\nand experience\", In Structural Assessment \u2013 The Role of Large and Full\nScale Testing, E & FN SPON, London 1997, pp. 301-308.", "M. Karmaz\u00ednov\u00e1, \"Design assisted by testing \u2013 a powerful tool for the\nevaluation of material properties and design resistances from test\nresults\", International Journal of Mathematical Models and Methods in\nApplied Sciences, Vol. 6, No. 2, 2012, pp. 376-385. ISSN 1998-0140.", "Eurocode 1: EN 1990 Basis of Structural Design: Annex D \u2013 Design\nassisted by testing (2nd Edition), CEN Brussels, 2011.", "Eurocode 3: EN 1993-1-1 Design of Steel Structures, Part 1-1: General\nRules and Rules for Buildings, CEN Brussels, 2008.\n[10] Eurocode 3: EN 1993-1-9 Design of Steel Structures, Part 1-9: Fatigue,\nCEN Brussels, 2012.\n[11] \u010cSN 73 1401 Design of Steel Structures, Czech Technical Institute for\nNormalization, Prague, 1998."]}